Anwā’ Mā Wa Ma’ānīha Fī Surah Al-Ahzab (Taqdir, 2024)
Nahwu science there are elements that are the subject of nahwu science is, isim, fi'il and harf. The objectives of this study include: 1. Knowing the types of letters Maa in Al-Ahzab. 2. Knowing the meaning of the letter Maa in the letter Al-Ahzab. This type of research is library research. Literature study is all efforts made by researchers in gathering information that is relevant to the topic or problem to be studied. Theories underlying the problems and areas to be studied can be found by conducting a literature study. The results obtained by researchers in their research are that researchers find several types of letters Maa and their meanings in Al-Ahzab letter, namely Maa Mausuliyah, found in 14 verses and 21 places. Maa Syartiyah, is contained in 1 verse. Maa Nafiyah, there are 13 places in 11 verses in surah Al-Ahzab. Maa Zaidah there are 2 verses in Surah Al-Ahzab. After observing the results of the research, the researcher advises the students of knowledge to pay attention to the science of nahwu, so that they understand the rules of the Arabic language because that is the basis for understanding the content in the Qur'an.